SCHOOLING AS A POSSIBLE SUCCESS FACTOR? A NOVEL INVESTIGATION OF DETERMINING FACTORS OF SUCCESS IN FOUR SUMMER OLYMPIC GAMES - István SOOS; Tibor KISS; Ian WHYTE; Pál HAMAR; Iuliana BOROS-BALINT; Attila SZABO (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2020)
The exploration of factors underpinning Olympic success (number of medals won) extended to the Human Development Index (HDI). Analysis of the Rio Olympic Games supported the influence of geographic and social variables. Schooling was one of the most important predictors and together with population explained 64%; when adding geographic variables (North-West and temperature) 67% of Olympic medals won were explained. This relationship was validated in the last four Olympic Games (from 2004 to 2016). This is the first study ever to demonstrate that specific social and geographical factors determine more than two thirds of the variance in Olympic success.